Parathyroid Hormone Polymorphism RS6254 is Associated with the Development and Severity of Osteoporosis in Asymptomatic but not Normocalcemic Hyperthyroidism - Díaz-Soto, G.; Romero, E.; Pérez-Castrillón, J. L.; Jauregui, O. I.; de Luis Román, D. (Hormone and Metabolic Research, 2016)
Although normocalcemic and asymptomatic hyperparathyroidism (HPT) are becoming more common, they remain only partially understood. Parathyroid hormone (PTH) polymorphisms have been associated with disease severity in classical HPT. The aim of the present study was to evaluate the clinical effect of PTH polymorphism (rs6254) in normocalcemic and asymptomatic HPT. A prospective study of 61 consecutive patients with normocalcemic or asymptomatic HPT was carried out. Secondary causes of HPT were ruled out. All patients were followed for≥1 year. Calcium and phosphorus metabolism parameters were assessed at least twice during the follow-up period to classify as normocalcemic or asymptomatic HPT. Bone mineral density (BMD) and the rs6254 polymorphism genotype were also assessed. Genotype rs6254GG was observed in 23 patients (37.7%) whereas GA and AA genotypes were presented in 29 (47.5%) and 9 (14.8%) patients, respectively. Age, sex and genotype distributions were comparable in both groups. In asymptomatic but not normocalcemic HPT patients, the GG genotype was associated with a significantly higher level of intact PTH [200.2 (SD 76.5) vs. 113.3 (SD 25.9) pg/ml; p<0.01], and significantly lower Z-score densitometry at the femoral neck, proximal femur, and lumbar spine. Both remained significant after adjusting for major confounding factors by multiple linear regression. The present study supports the independent pathogenic effect of rs6254GA polymorphism on the development and severity of BMD complications in patients with asymptomatic but not normocalcemic HPT. Further studies are needed to confirm this finding and to assess the effect of other polymorphisms in normocalcemic and asymptomatic HPT.
Keywords: parathyroid hormone; parathyroid hormone gene; vitamin D; hyperparathyroidism